Safety-Critical Attitude Tracking of Spacecraft With Data-Based Parameter Identification - Xia, Kewei; Wang, Jianan; Liu, Fuxiang (IEEE transactions on aerospace and electronic systems, 2025)
This article proposes a safety-critical control strategy for the attitude tracking issue of a rigid spacecraft subject to orientation and angular velocity constraints. To compensate for the unknown inertial matrix parameters, an online identification algorithm with a data-based selection criteria is first designed, which shows that the estimate error is exponentially convergence if a finite excitation condition is satisfied. Then, by introducing the identified parameters, an adaptive hybrid attitude tracking control torque is developed, where a binary logic switch framework is employed to avoid the unwinding phenomenon. For the sake of safety-critical tracking subject to state constraints, a control barrier function quadratic programming optimization is developed, where the nonconvex orientation constraints are losslessly replaced by convex quadratic ones. The uniform asymptotic stability of the closed-loop system is proved, and the preassigned safety sets are forward invariant with the largest safe region. Simulation results validate and access the proposed control strategy.